by property of determinant
a b-c c+b
a+c b c-a
a-b b+a c =​(a+b+c)(a^2+b^2+c^2)

Let  = ab-cc+ba+cbc-aa-ba+bcApply C1 = aC1; C2 = bC2; C3 = cC3 and divide the  by abc, we get = 1abca2b2-bcc2+bca2+acb2c2-aca2-abab+b2c2Applying C1 = C1 + C2 + C3, we get = 1abca2+b2+c2b2-bcc2+bca2+b2+c2b2c2-aca2+b2+c2ab+b2c2 = a2+b2+c2abc1b2-bcc2+bc1b2c2-ac1ab+b2c2Applying R1 = R1 - R2 and R2 = R2 - R3, we get = a2+b2+c2abc0-bcbc+ac0-ab-ac1ab+b2c2 = a2+b2+c2abc 1abc2 + abbc+ac = a2+b2+c2abcabc2+ab2c+a2bc = a2+b2+c2abc × abcc+b+a =a2+b2+c2a+b+c

  • 33
What are you looking for?